2003
DOI: 10.1111/j.1460-2466.2003.tb03008.x
|View full text |Cite
|
Sign up to set email alerts
|

Alienation, Aggression, and Sensation Seeking as Predictors of Adolescent Use of Violent Film, Computer, and Website Content

Abstract: Use of violent media content by adolescents has long been a matter of public concern and debate, a concern that was heightened by the reported use of violent computer games and websites by the killers at Columbine High School in 1999. This study examined predictors of various types of self-reported use of violent media content by 8th graders (N = 3,127) from 20 schools around the U.S. Hierarchical regression analyses indicated that gender, sensation seeking, aggression, and frequency of Internet use had relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(62 citation statements)
references
References 20 publications
4
54
1
3
Order By: Relevance
“…We used a 4-point scale, 0 = never, 1 = sometimes, 2 = often, and 3 = always. Similar to other media use measures (e.g., Gil de Zúñiga, Jung, & Valenzuela, 2012;Slater, 2003), this measure of SM use can best be seen as an index of how often someone uses SM rather than a reflective scale. The items in this scale are more likely to be compensatory rather than exchangeable.…”
Section: Methodsmentioning
confidence: 99%
“…We used a 4-point scale, 0 = never, 1 = sometimes, 2 = often, and 3 = always. Similar to other media use measures (e.g., Gil de Zúñiga, Jung, & Valenzuela, 2012;Slater, 2003), this measure of SM use can best be seen as an index of how often someone uses SM rather than a reflective scale. The items in this scale are more likely to be compensatory rather than exchangeable.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that females in general have a low preference for observing or taking part in violent conflicts and resolutions, show in their media genre preferences in general less interest than males in violent entertainment and prefer non-violent entertainment [15]. As most computer games involve to a large extent and increasingly realistic violence and violent actions, it is not surprising that this is an important factor of females' dislike of games [9].…”
Section: Computer Games and Gender Differencesmentioning
confidence: 99%
“…defined as Ba relatively enduring organization of beliefs, feelings, and behavioral tendencies towards socially significant objects, groups, events or symbols^ [32]. This approach is supported by a broad body of evidence on the influence of affective, cognitive and behavioral factors on individuals quality judgment of and emotional response to media [55,60,75,87,96,105].…”
Section: The Media Experience: Presence Emotions and Quality Judgmentmentioning
confidence: 96%